Relative importance of inflammatory markers in deciding infection versus inflammation - Chakrabartty, Subroto; Sardar, Ajit; Ghosh, Aniruddha; Barman, Santanu (International Journal of Advances in Medicine, 2018)
Background: Fever is the commonest presentation of pediatric patients attending emergency departments of all children’s hospital. The cause of fever may be acute bacterial infections or primary vasculitic disorders like Kawasaki disease or inflammation due to non-bacterial infections. The objective was to compare the performance of the four biomarkers ESR, CRP, Procalcitonin and IL-6 in predicting a diagnosis of sepsis/infection and find out a definite cut off value for the statistically most significant one. Methods: The authors conducted this prospective observational study at the indoors of a pediatric tertiary care referral center in India to find out a biomarker which can differentiate between infection and inflammation (vasculitis) in children admitted with fever and finally diagnosed as infection or inflammation (vasculitis). Results: Among ESR, CRP, Procalcitonin and Interleukin-6, only IL-6 showed statistical significance in differentiating infection from inflammation (vasculitis) analysed using the Receiver Operating Characteristic (ROC) curve and Mann-Whitney U test, sensitivity and specificity. Conclusions: IL-6 level 27 pg/mL or less at the time of admission indicates an infectious etiology while level more than this indicates towards a vasculitic cause.